Selenium and vitamin E interaction in the nutrition of yellowtail kingfish (Seriola lalandi): Physiological and immune responses - Le, K.; Fotedar, Ravi; Partridge, G. (John Wiley & Sons Ltd, 2013)
Six dietary treatments were prepared in a 3 × 2 factorial design (unsupplemented or supplemented with Se at 1 or 2 mg kg-1 × supplemented with vitamin E at 40 or 180 mg kg-1) and fed to yellowtail kingfish (Seriola lalandi) for 6 weeks to evaluate the effects of dietary Se and vitamin E on growth performance, immune and antioxidant responses and to investigate the potential interaction between these two micronutrients in this species. The results have revealed significantly interactive effects with positive physiological responses. Se significantly increased weight gain of fish fed diets low in vitamin E, but not high in vitamin E, whereas serum lysozyme activity was significantly improved by Se in diets high in vitamin E, but not low in vitamin E. Moreover, there was evidence of myopathy in fish deficient in both Se and vitamin E, but not single deficiency. There was no significant effect of dietary Se, vitamin E or their interaction on survival, antibody titre, feed intake, feed conversion ratio and fillet proximate composition; however, fillet Se and vitamin E were significantly responsive to dietary Se and vitamin E, respectively, and higher dietary Se intakes produced significantly higher red blood cell glutathione peroxidase activity.